IMPLEMENTASI OEE UNTUK PENGUKURAN KINERJA MESIN PRODUKSI KAIN KERAS DAN PENINGKATANNYA MENGGUNAKAN METODE FMEA DI PT MMI (Universitas Esa Unggul, 2018)
AbstractPT MegahMegalon Industries is a company engaged in non-woven interlining, a company that produces non-woven fabrics or better known as hard fabrics. PT MegahMegalon Industries has 2 production lines. The problem that is often experienced is the ineffectiveness of the machine's performance. For this reason, the effectiveness of the machine is measured using the Overall Equipment Effectiveness method for both lines. The OEE value in line 2 is 83.19% and line 3 is 82.28%. The reason why the OEE value line 2 is not ideal is due to the Quality Ratio which is dominated by Dirty Black Oil Defect, while Line 3 is due to the Availability Ratio which is dominated by Breakdown Carding A due to a broken needle. Then a cause and effect analysis is made to find out the causes of the defects and breakdowns above by brainstorming on the company, which is known to be 11 causes of each problem. Furthermore, a Matrix Diagram is made to determine the Critical To Quality of the causes of the problem and there are 4 dominant causes of defects and 3 dominant causes of breakdowns. The dominant causes that have been identified, a Failure Mode And Effect Analysis was made to determine the proposed improvements that could be made. FMEA is made in collaboration with the team to determine the Risk Priority Number value. Among FMEA defects and breakdowns, the highest RPN value. Defect was minimal cleaning equipment, while breakdown was the operator mishandling the cylinder. Keywords : overall equipment effectivness, diagram matrix, critical to quality AbstrakPT Megah Megalon Industries adalah perusahaan yang bergerak dalam bidang interlining non-woven yaitu perusahaan yang menghasilkan kain non-woven atau lebih dikenal dengan kain keras. PT Megah Megalon Industries memiliki 2 lini produksi. Permasalahan yang sering dialami adalah ketidakefektifan kinerja mesin, untuk itu dilakukan pengukuran keefektifitasan mesin dengan menggunakan metode Overall Equipment Effectivness terhadap kedua lini. Nilai OEE pada lini 2 yaitu 83,19% dan lini 3 adalah 82,28%. Penyebabtidakidealnyanilai OEE lini 2 disebabkanQuality Ratio yang didominasi oleh Defect Kotor Hitam Oli, sedangkan Lini 3 karena Availability Ratio yang didominasi Breakdown Carding A karena jarum patah. Kemudian dibuatlah analisis sebab akibat untuk mengetahui penyebab defect dan breakdown diatas dengan brainstorming pada pihak perusahaan yang mana diketahui terdapat 11 penyebab dari masing – masing permasalahan. Selanjutnya dibuat Diagram Matrix untuk mengetahui Critical To Quality dari penyebab – penyebab permasalahan dan didapatkan 4 penyebab dominan defect, dan 3 penyebab dominan breakdown. Penyebab – penyebab dominan yang sudah diketahui, dibuatkan Failure Mode And Effect Analysis untuk mengetahui usulan perbaikan yang dapat dilakukan. FMEA dibuat bekerjasama dengan tim untuk menentukan nilai Risk Priority Number. Diantara FMEA defect dan breakdown, Nilai RPN tertinggi Defect adalah alat kebersihan yang minim, sedangkan breakdown adalah operator salah penanganan silinder. Kata kunci : overall equipment effectivness, diagram matrix, critical to quality